5-Aminosalicylic acid is a potent inhibitor of interleukin 1 beta production in organ culture of colonic biopsy specimens from patients with inflammatory bowel disease. Issue 1 (January 1991) - Mahida, Y R; Lamming, C E; Gallagher, A; Hawthorne, A B; Hawkey, C J
Abstract : Interleukin 1 beta in biopsy specimens from inflamed colonic mucosa of patients with active inflammatory bowel disease was studied. Compared with normal colonic mucosal biopsy specimens, a significantly greater amount of interleukin 1 beta was present in rectal mucosa before (median (range) 4.3 (2.0-11.8) v 119.2 (30.1-286.8) pg/mg; p less than 0.01) and produced during organ culture (39.1 (9.4-106.8) v 97.6 (28.2-991.6) pg/mg; p less than 0.01). Values of interleukin 1 beta after culture correlated with concentrations of thromboxane B2. Organ culture of inflamed biopsy specimens in the presence of 5 aminosalicylic acid and dexamethasone reduced the amount of interleukin 1 beta detected. At the doses studied, 5 aminosalicylic acid also reduced the amount of leukotriene B4 detected after culture.